2022
DOI: 10.3390/life12071086
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Intense Pulsed Light Therapy and Meibomian Gland Expression for Evaporative Dry Eye

Abstract: Dry eye disease (DED) is most commonly caused by evaporative subtypes and mainly induced by meibomian gland dysfunction (MGD). Intense pulsed light (IPL) combined with meibomian gland expression (MGX) is a noninvasive treatment for improvement of ocular discomfort symptoms and MGD. In this prospective study between November 2020 and May 2022, the patients with MGD and abnormal meibomian expressibility that met the criteria of both ocular surface disease index (OSDI) ≥ 13 scores and standardized patient evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In step 2, the two horizontally oriented and overlapped shots were applied from the main IPL crystal at the area over a lower tarsus one time. In step 3, the small-sized but tall tip (15…”
Section: Methods Of the Performance Of Ipl Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In step 2, the two horizontally oriented and overlapped shots were applied from the main IPL crystal at the area over a lower tarsus one time. In step 3, the small-sized but tall tip (15…”
Section: Methods Of the Performance Of Ipl Therapymentioning
confidence: 99%
“…Moreover, recent several clinical trials revealed the therapeutic efficacy of the protocolized IPL therapy combined with the meibomian gland expression (MGX) for the treatment of MGD [13][14][15][16]. Although those studies set up the fixed regular, steady, and continuous IPL treatment protocol to evaluate its therapeutic efficacy, in real-world situations, the rapid symptomatic improvement or the patient's dissatisfaction with the treatment might terminate the protocol early unexpectedly.…”
Section: Introductionmentioning
confidence: 99%